Islamic Boarding School Design - Firmansyah Firmansyah; Wowo Adizar Darwin; Husna Izzati (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2022)
The term Islamic Boarding School may be familiar to our ears. The existence of Islamic Boarding Schools has recently mushroomed and has become an attraction for some people. Boarding School is a pre-university level boarding school where all students live in dormitories that have been provided for the duration of their education. We all know that socializing in this millennial era is a scourge for parents, especially for those whose children are in their teens, the presence of the Islamic Boarding School is the answer to these problems, not just a choice but also a need for parents